Association of leisure-time physical activity and resistance training with risk of incident hypertension: The Ansan and Ansung study of the Korean Genome and Epidemiology Study (KoGES) - Park, Jae Ho; Lim, Nam-Kyoo; Park, Hyun-Young (Frontiers in Cardiovascular Medicine, 2023)
Hypertension is the most common risk factor for the incidence of and mortality associated with cardiovascular disease. We aimed to investigate the association between incident hypertension and 4-year leisure-time physical activity (PA) and resistance training (RT) levels. In this community-based Korean cohort, 5,075 participants without hypertension were included. To evaluate cumulative PA, the average PA time (the total time of moderate-intensity leisure-time PA) at baseline, 2-year follow-up, and 4-year follow-up were calculated. Participants were categorized into four groups based on their participation in RT and adherence to PA guidelines (≥150 min/week of PA time) as follows: Low-PA, Low-PA+RT, High-PA, and High-PA+RT. A multivariate Cox proportional hazards regression model was used to assess the 12-year incidence of hypertension according to leisure-time PA levels and RT regularity. During a mean 7.86 ± 4.20-year follow-up, 2,544 participants (1,366 women) were diagnosed with hypertension. Compared with Low-PA, High-PA and High-PA+RT decreased the risk for hypertension by 30% and 39%, respectively. Participation in RT without compliance to PA guidelines did not affect the incidence of hypertension. We further analyzed the additive effect of RT on hypertension in the High-PA group. Although sex-based comparisons indicated that men had a significantly longer training period for RT than women, an additional reduction in the risk for hypertension in relation to the addition of RT was observed only in women (35%). PA may confer protective effects against hypertension, whereas the addition of RT to high levels of PA can further decrease the risk for hypertension in women.